Behind the official website of the Metropolis of Moldavia and Bukovina - philosophy and the sources of inspiration - Rusu, Tudorel-Constantin (Technium Social Sciences Journal, 2022)
The phenomenon of Christianity on the Internet is widely known and appreciated by most Christian faithful and priests for quite a long time, even though in the beginning it was met with distrust. This proves, once again, that there is no medium of communication totally incompatible with the “Good News” - the Gospels. Regarding the online presence of the Romanian Orthodox Church in general and of the Metropolis of Moldavia and Bukovina in particular, it became clearly evident that a web platform representing the Church, besides its spiritual and dogmatic rigours, had to align itself with the expectations and online habits of the public - in this case of the faithful - to ensure their engagement. That’s why I consider it significant to present the philosophy and some of the initial sources of inspiration that led to the success of Doxologia.ro, the official website of the Metropolis of Moldavia and Bukovina, which has now the most readers (an average of 97.027 unique users daily in 2021) of the official and private religious sites in Romania. Thus, my main research questions are: Why is the web platform Doxologia.ro a special case regarding Christian mass media in Romania? What are the major concepts from which the platform started? Finally, how can a Christian bimillennial tradition be user friendly?